The Impact of CPTTP on Accessing Medicine in Thailand - Leelaprathuang, Natkritta (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2021)
The Comprehensive and Progressive Agreement of Trans-pacific Partnership (CPTPP) is becoming an interesting issue among countries including Thailand. At present, Thailand is in the process of studying the benefits and the drawbacks of this agreement to decide whether Thailand should join this agreement. It can be seen that there are both advantages and disadvantages. The anticipated advantages that Thailand will receive are the growth of trade opportunities, the growth of export and investment capabilities, and the growth of competition efficiency. However, CPTPP also create the negative impacts on Thailand in many aspects. For instance, in the aspect of investment, CPTPP allows foreign investors to compete with Thai investors freely while in fact Thai investors may not have sufficient capacity to compete with foreign investors. In the aspect of agricultural industry, Thailand must participate in the International Union for the Protection of New Varieties of Plants (UPOV1991), affecting agriculturist or farmer in Thailand. In the aspect of development of country, the agreement in CPTPP might be a barrier for Thailand to achieve the Sustainable Development Goals in 2030. The significant aspect that CPTPP also impacts on is, especially drug patent, accessing medicine. Thus, this article aims to analyze the impact of CPTTP on accessing medicine in Thailand.